Coprinopsis roseolofusca (Psathyrellaceae, Agaricales), a new species from Spain and Hungary - Voto, Pietro; Nagy, László G.; Suárez, Eleazar (Phytotaxa, 2026)
Based on two European collections and an ITS phylogenetic analysis, Coprinopsis roseolofusca sp. nov. is described based on morphology and ITS phylogenetic analysis. It had already been isolated by Nagy in 2012 as Coprinopsis aff. krieglsteineri from Hungary. Voto’s recent study of a Spanish collection by Suárez highlighted the connection between the two materials. The new species is characterized by a delicate lilac-pinkish pileus with a dark purplish brown disc and a copious fibrillose-flocculent hairy velar covering, collared gills, and nodulose to diverticulate hyphae in the stipe veil. The veil was also initially present on the pileus. The collaboration that followed ultimately led to the description of this new species. A full description, illustrations, and phylogenetic analysis results of the new species are presented.